Endometriosis and Ovarian Cancer Risk: A Systematic Review of Epidemiological Studies - Zafrakas, Menelaos; Grimbizis, Grigorios; Timologou, Anna; Tarlatzis, Basil C. (Frontiers in Surgery, 2014)
Background: A possible etiological association between endometriosis and ovarian cancer has been repeatedly reported in the literature. Objective: Our aim was to evaluate published epidemiological data on this issue. Review Methods: We conducted an extensive search of the literature in MEDLINE, of articles ever published until February 2014, using the key-words “endometriosis” and “ovarian” and one of the following terms in the title: “cancer” or “malignancy” or “malignant” or “tumor” or “tumour” or “neoplasia” or “neoplasm” or “transformation”. Retrieved papers were checked for further relevant publications. Results: Overall, our search yielded one prospective cohort study, ten retrospective cohort and five case-control studies. A meta-analysis of these studies was not considered to be appropriate, due to differences in data reporting, study design and adjustment for confounding factors. Limitations: The main limitation of studies found, with one exception, was the lack of operative confirmation of endometriosis. Conclusions: An association of endometriosis with clear-cell and endometrioid ovarian cancer was a consistent finding in most studies. On the other hand, existing epidemiological evidence linking endometriosis with ovarian cancer is insufficient to change current clinical practice. Prospective cohort studies, with prior laparoscopic confirmation, localization and staging of endometriosis are needed, in order to further clarify this issue.